2014
DOI: 10.5056/jnm.20.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Non-erosive Reflux Disease and High Risk of Obstructive Sleep Apnea in Korean Population

Abstract: Background/AimsObstructive sleep apnea is becoming more important in gastroesophageal reflux disease (GERD) patients. This study investigated the prevalence of high risk for obstructive sleep apnea in GERD patients in comparison with that in healthy controls using the Berlin Questionnaire. We also investigated the risk factors for obstructive sleep apnea in GERD patients. MethodsWe enrolled 1,007 subjects: 776 healthy controls, 115 individuals with erosive reflux disease, and 116 with non-erosive reflux diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…When controlling for variables, the risk of poor sleep quality was significantly increased for individuals with GERD compared with controls . A study performed in Korea indicated that individuals with GERD were likely to be at high risk for OSA compared to the control group (28.2% vs. 20.4%; P = 0.036) …”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…When controlling for variables, the risk of poor sleep quality was significantly increased for individuals with GERD compared with controls . A study performed in Korea indicated that individuals with GERD were likely to be at high risk for OSA compared to the control group (28.2% vs. 20.4%; P = 0.036) …”
Section: Epidemiologymentioning
confidence: 99%
“…Among 33,391 patients with symptomatic GERD, 64% of them had nGER symptoms that were associated with sleep disturbances . In a study performed in Korea that compared GERD ( n = 231) defined by upper endoscopy and/or frequent typical symptoms and controls ( n = 776), the prevalence of nGER symptoms was higher in GERD patients than in controls (23.4% vs. 4.1%; P < 0.001) . Among 9322 patients with heartburn or regurgitation, 84% reported sleep disturbances because of nGER reflux, including reflux in the supine position (72%), typical reflux disturbing sleep (39%), and waking because of reflux (45%) …”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported a high prevalence of RE in patients with OSAS, including some which used questionnaires to diagnose it [23,29]. However, many studies have reported no association between OSA severity and GER.…”
Section: Risk Factors For Re In Non-obese Patients With Osasmentioning
confidence: 99%